Assessing the contribution of callous–unemotional traits and affective empathy to aggressive behaviour among teenagers hosted in a youth protection centre - Giroux, Samuel (Psychology, crime & law, 2022)
Proactive aggressive behaviour (PA) refers to violent and intentional behaviours with serious consequences. Adolescents entrusted by law to youth protection centres are at risk of this type of behaviour. To understand their behaviour, several factors have to be considered (i.e. reactive aggressive behaviour (RA), gender differences, externalized disorders). More importantly, callous–unemotional (CU) traits and lack of empathy can have an impact either way, but their contribution needs to be better understood. The objective of this study is to document the relationships between these factors and PA and to measure their contribution. A total of 87 teenagers living in a youth protection centres (53.5% girls and 46.5% boys), aged between 13 and 18, took part in the study. Results showed positive correlation between PA and RA, oppositional defiant disorder, conduct disorder and CU traits, as well as negative correlation between PA and affective empathy. Hierarchical regression analyses confirm that CU traits and affective empathy remain contributing factors in a unique way. Our results highlight the importance of taking into account the adolescent’s capacity to feel emotions towards others in order to better assess, understand and act upon their aggressive behaviour.